Urachal carcinoma: a large retrospective multicentric study from the French Genito-Urinary Tumor Group - Guerin, M.; Miran, C.; Colomba, E.; Cabart, M.; Herrmann, T.; Pericart, S.; Maillet, D.; Neuzillet, Y.; Deleuze, A.; Coquan, E.; Laramas, M.; Thibault, C.; et al. (Frontiers in Oncology, 2023)
Introduction: Urachal cancer (UrC) is a rare, non-urothelial malignancy. Its natural history and management are poorly understood. Although localized to the bladder dome, the most common histological subtype of UrC is adenocarcinoma. UrC develops from an embryonic remnant, and is frequently diagnosed in advanced stage with poor prognosis. The treatment is not standardized, and based only on case reports and small series. This large retrospective multicentric study was conducted by the French Genito-Urinary Tumor Group to gain a better understanding of UrC. Material and Methods: data has been collected retrospectively on 97 patients treated at 22 French Cancer Centers between 1996 and 2020. Results: The median follow-up was 59 months (range 44-96). The median age at diagnosis was 53 years (range 20-86), 45% were females and 23% had tobacco exposure. For patients with localized disease (Mayo I-II, n=46) and with lymph-node invasion (Mayo III, n=13) median progression-free-survival (mPFS) was 31 months (95% CI: 20-67) and 7 months (95% CI: 6-not reached (NR)), and median overall survival (mOS) was 73 months (95% CI: 57-NR) and 22 months (95% CI: 21-NR) respectively. For 45 patients with Mayo I-III had secondary metastatic progression, and 20 patients were metastatic at diagnosis. Metastatic localization was peritoneal for 54% of patients. Most patients with localized tumor were treated with partial cystectomy, with mPFS of 20 months (95% CI: 14-49), and only 12 patients received adjuvant therapy. Metastatic patients (Mayo IV) had a mOS of 23 months (95% CI: 19-33) and 69% received a platin-fluorouracil combination treatment. Conclusion: UrC is a rare tumor of the bladder where patients are younger with a higher number of females, and a lower tobacco exposure than in standard urothelial carcinoma. For localized tumor, partial cystectomy is recommended. The mOS and mPFS were low, notably for patients with lymph node invasion. For metastatic patients the prognosis is poor and standard therapy is not well-defined. Further clinical and biological knowledge are needed.